2019
DOI: 10.18311/mvpjms/2018/v5i2/11030
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficacy and Success Rate of Single Dose Oral Mifepristone and Vaginal Misoprostol v/s Vaginal Misoprostol alone for Second Trimester Termination of Pregnancy

Abstract: Background: Second trimester abortions constitute 10-15% of all induced abortions and are considered to be less safe than first trimester abortions. The combination of mifepristone and misoprostol is now an established and highly effective method for second trimester abortion. Aim: To compare the efficacy and the success rate of single dose oral mifepristone plus vaginal misoprostol versus vaginal misoprostol alone for second trimester termination of pregnancy. Materials and Methods: A comparative study and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Some studies have shown that higher effectiveness of drugs administered was observed via vaginal route rather than oral one. [ 8 14 ] A study by Khairnar and Patil[ 15 ] stated that if the dose and the interval of drug administration in the sublingual and vaginal methods are correctly implemented, similar results on the efficacy of the drug for two routes are observed. The study by Imširija et al [ 16 ] indicated that there is no valuable research showing the comparison of effectiveness between the vaginal and oral methods during weeks 9 and 12 of pregnancy; however, overall, more success rate has been reported for the vaginal method.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that higher effectiveness of drugs administered was observed via vaginal route rather than oral one. [ 8 14 ] A study by Khairnar and Patil[ 15 ] stated that if the dose and the interval of drug administration in the sublingual and vaginal methods are correctly implemented, similar results on the efficacy of the drug for two routes are observed. The study by Imširija et al [ 16 ] indicated that there is no valuable research showing the comparison of effectiveness between the vaginal and oral methods during weeks 9 and 12 of pregnancy; however, overall, more success rate has been reported for the vaginal method.…”
Section: Discussionmentioning
confidence: 99%